2012
DOI: 10.1097/meg.0b013e328354fc83
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic vomiting syndrome in 28 patients

Abstract: CVS is a debilitating illness with frequent attacks of prolonged duration. There is a high association with anxiety/depression as well as headaches. Antimigraine medication, β-blockers and antiepileptic treatment may be successful at attenuating attacks; however, in this long-term study, the prognosis of patients not treated with these medications was also good. Overall, 61.9% of patients showed a gradual improvement in symptoms and 23.8% had complete resolution after a mean of 7 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…CHS is a syndrome of cyclic episodes of nausea, vomiting, and abdominal pain associated with chronic cannabis usage. CHS is frequently confused with cyclic vomiting syndrome, which has similar features 76 . An interesting and poorly understood feature of the syndrome is that patients report reduced symptoms following hot baths or showers 75, 77, 78 .…”
Section: Endocannabinoids In the Control Of Nausea And Vomitingmentioning
confidence: 99%
“…CHS is a syndrome of cyclic episodes of nausea, vomiting, and abdominal pain associated with chronic cannabis usage. CHS is frequently confused with cyclic vomiting syndrome, which has similar features 76 . An interesting and poorly understood feature of the syndrome is that patients report reduced symptoms following hot baths or showers 75, 77, 78 .…”
Section: Endocannabinoids In the Control Of Nausea And Vomitingmentioning
confidence: 99%
“…Each episode can last from a few hours to several days. Between the attacks, the patients are healthy and symptom-free [ 1 4 ]. Multiple triggering factors have been proposed for acute emetic episodes.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology is unknown, but it is possibly because of a dysregulation of the neuroendocrine system, exaggerated cardiovascular responses to postural change and other stimuli that may be associated with the onset of gastrointestinal symptoms. 2 A 27-month-old patient reported to the department of paediatric dentistry with symptoms of swollen gums and loose teeth in the lower front teeth region (figure 1). A detailed history revealed that the patient suffered from repeated episodes of fever and vomiting and was diagnosed with CVS.…”
Section: Descriptionmentioning
confidence: 99%